Formulasi Sediaan Krim Sari Buah Mangga Harum Manis (Mangifera Indica L.) Sebagai Pelembab Kulit Dan Tabir Surya - Putri Elvia Sari; Mamik Ponco Rahayu; Anita Nilawati (Fakultas Farmasi Universitas Setia Budi, 2025)
UV rays can cause wrinkles, dryness and spots so the skin needs sunscreen nutrition. Sweet fragrant mango fruit contains flavonoids, tannins, and vitamin c as potential sunscreen. This study aims to formulate mango juice as a moisturising and sunscreen cream preparation in the form of hand cream. Mango fruit juice was extracted using a juicer and dried with a freeze dryer, then formulated into creams with concentrations of 2.5%; 5%; 7.5%; 10%. The preparation was evaluated for physical quality and tested for anti- irritation activity, moisture, and SPF value using a spectrophotometer. Data were statistically analysed using SPSS One Way Anova. The results showed that mango juice contains flavonoids, tannins, and vitamin C compounds. The cream formula fulfils the physical quality evaluation requirements of the preparation, does not irritate and has skin moisture activity. Formula 4 is the most effective cream preparation in moisturizing the skin with a moisture percentage of 72% but does not have SPF activity.